PENGARUH EMPLOYABILITY SKILLS TERHADAP KESIAPAN KERJA SISWA - Tsaqib, Ahmad Faishal; Wiyono, Agus; Rusimamto, Puput Wanarti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research is motivated by the gap between the competencies of Vocational High School (SMK) graduates and the demands of the industrial world, where many students are deemed to lack adequate work readiness. The focus of this study is to quantitatively analyze the influence of employability skills—which include non-technical competencies such as communication and cooperation—on students' work readiness. As a crucial step, this study used a quantitative approach with an associative design on 100 students. Data were collected through a valid and reliable questionnaire and then analyzed using simple linear regression. The main findings indicate that employability skills have a positive and statistically significant influence on work readiness (p < 0.05). The resulting quantitative regression model confirms that any increase in employability skills mastery will increase students' work readiness levels. In conclusion, employability skills mastery is a crucial predictor of the work readiness of SMK graduates. These findings emphasize the urgency for vocational education institutions to systematically integrate non-technical skills development into the curriculum as a core component to bridge the gap with industry needs. ABSTRAKPenelitian ini dilatarbelakangi oleh adanya kesenjangan antara kompetensi lulusan Sekolah Menengah Kejuruan (SMK) dengan tuntutan dunia industri, di mana banyak siswa dinilai kurang memiliki kesiapan kerja yang memadai. Fokus penelitian ini adalah untuk menganalisis secara kuantitatif pengaruh employability skills—yang mencakup kompetensi non-teknis seperti komunikasi dan kerja sama—terhadap kesiapan kerja siswa. Sebagai langkah penting, penelitian ini menggunakan pendekatan kuantitatif dengan desain asosiatif pada 100 siswa, di mana data dikumpulkan melalui kuesioner yang valid dan reliabel, kemudian dianalisis menggunakan regresi linier sederhana. Temuan utama menunjukkan bahwa employability skills memiliki pengaruh yang positif dan signifikan secara statistik terhadap kesiapan kerja (p < 0,05). Model regresi yang dihasilkan secara kuantitatif menegaskan bahwa setiap peningkatan pada penguasaan employability skills akan meningkatkan tingkat kesiapan kerja siswa. Kesimpulannya, penguasaan employability skills merupakan prediktor krusial bagi kesiapan kerja lulusan SMK. Temuan ini menegaskan urgensi bagi lembaga pendidikan kejuruan untuk secara sistematis mengintegrasikan pengembangan keterampilan non-teknis ke dalam kurikulum sebagai komponen inti untuk menjembatani kesenjangan dengan kebutuhan industri.